The Impact of Oxygen at Various Stages of Vinification on the Chemical Composition and the Antioxidant and Sensory Properties of White and Red Wines - Tomasz Tarko; Aleksandra Duda-Chodak; Paweł Sroka; Małgorzata Siuta (International Journal of Food Science)
The purpose of this review was to collect and systematize information on the role and importance of oxygen in winemaking. Both the positive and negative effects of oxygen are presented and discussed throughout the text. The review characterizes the subsequent stages of the wine production process, during which oxygen comes into contact with fruits, must, and finally wine. The impact of oxygen on the growth and metabolism of yeast, on the activity of enzymes, and on the final quality of wine was presented. The discussion of the effect of oxygen presence on the taste, aroma, colour, and stability contains a detailed description of changes of volatile compounds, polyphenols, and other important components of wine that take place in the presence of oxygen in both white and red wines. New techniques based on the use of oxygen to obtain the desired sensory characteristics of wine were also presented.